2013
DOI: 10.1111/ppl.12061
|View full text |Cite
|
Sign up to set email alerts
|

Nep1‐like protein from Moniliophthora perniciosa induces a rapid proteome and metabolome reprogramming in cells of Nicotiana benthamiana

Abstract: NEP1 (necrosis- and ethylene-inducing peptide 1)-like proteins (NLPs) have been identified in a variety of taxonomically unrelated plant pathogens and share a common characteristic of inducing responses of plant defense and cell death in dicotyledonous plants. Even though some aspects of NLP action have been well characterized, nothing is known about the global range of modifications in proteome and metabolome of NLP-treated plant cells. Here, using both proteomic and metabolomic approaches we were able to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…Protein identification was performed using a Mascot server (Version 2.1.04, Matrix Science) and the T. cacao genome database [68] . The search criteria used were trypsin digestion, variable modifications set as cysteine (Cys) and methionine (Met), max of one missed cleavages allowed and peptide mass tolerance of ±0.3 Da for the parent ion and 0.10 Da for the fragment ions [66] , [67] .…”
Section: Methodsmentioning
confidence: 99%
“…Protein identification was performed using a Mascot server (Version 2.1.04, Matrix Science) and the T. cacao genome database [68] . The search criteria used were trypsin digestion, variable modifications set as cysteine (Cys) and methionine (Met), max of one missed cleavages allowed and peptide mass tolerance of ±0.3 Da for the parent ion and 0.10 Da for the fragment ions [66] , [67] .…”
Section: Methodsmentioning
confidence: 99%
“…This indicates interference in the pathosystem because of overexpression of cystatins, and may interfere with symptom development and disease progression, which is directly related to cellular death induced by MpNEP2. Villela-Dias et al (2014) observed responses similar to necrosis in cell cultures of N. benthamiana (expressing green fluorescent protein) treated with MpNEP2, which is characterized by swelling of organelles and plasma membrane rupture among other processes, indicating direct damage to the plasma membrane. Studies by Mandal et al (2006) confirmed that cystatin expression can neutralize the effect of fungal proteases and block PCD during pathogenesis of the fungus.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies have demonstrated that recombinant MpNEP2 induces cell death in the leaves and tobacco suspension cell culture (Garcia et al, 2007) as well as reprograms the proteome and metabolome of Nicotiana benthamiana cells (Villela-Dias et al, 2014). In this study, we produced tobacco plants that overexpressed a cystatin gene sequence from cocoa (Tccys4).…”
Section: Introductionmentioning
confidence: 99%
“…were excised from gels and placed in microtubes. Then, they were bleached and subjected to trypsin digestion [ 23 ]. Next, the samples containing recovered peptides were vacuum concentrated until they reached a volume of 10–15 μL.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting peptides from tryptic digestion were subjected to liquid chromatography with tandem mass spectrometry (LC-MS/MS) on a nanoAcquity system (Waters, Milford, MA) coupled with a Q-ToF micro mass spectrometer (Waters), according to methods described elsewhere [ 23 ]. The raw data were processed, and the resulting spectra were analyzed in the ProteinLynx Global Server 4.2 software (Waters) and compared with the SwissProt database ( http://www.uniprot.org/downloads , October 2011).…”
Section: Methodsmentioning
confidence: 99%